Jointed Masonry Model: A constitutive law for 3D soil-structure interaction analysis. (15th December 2019) - Lasciarrea, Wanda G.; Amorosi, Angelo; Boldini, Daniela; de Felice, Gianmarco; Malena, Marialaura
Highlights: A 3D nonlinear constitutive model is proposed for the structural analysis of masonry structures. Soil-structure interaction problems are investigated through the implementation of the model into the geotechnical finite element code Plaxis 3D. The model is validated through comparison with some selected benchmark problems. The effect of tunnel excavation under different configurations of 3D masonry structures is investigated. Abstract: Classical approaches to soil-structure interaction are often characterised by relatively simple constitutive assumptions for either one or both components of the problem. Such simplified assumptions prove to be appropriate for simple soil-foundation cases, while showing all their limits when tackling more complex problems, as those involving excavation in the vicinity or beneath historical masonry structures. In such cases, the need for reliable prediction of the potential damage induced by construction activities on surface structures justifies the adoption of more advanced numerical approaches, possibly based on realistic constitutive assumptions for both soils and masonries, together with an accurate modelling schematisation of the excavation process. In recent years the Authors have adopted an advanced numerical approach to investigate this issue in the two-dimensional domain, accounting for the non-linearity and irreversibility of the soil behaviour and schematising the block masonry structure as a homogenised anisotropic medium. This study extends this approach to three dimensional conditions, to more realistically account for a number of features, including the possible different relative orientations between the structure and an underground tunnel under construction. The focus in this contribution is on the modelling of the masonry, here described by a modified version of the Jointed Rock model, an anisotropic elastic perfectly plastic constitutive model based on a simplified multilaminate approach and implemented in the commercial code Plaxis 3D. This model takes into account the directional properties of the medium, identifying the orientation of three planes along which the Mohr-Coulomb yield criterion applies. Here we first describe the modification introduced in the original model and then illustrate some benchmark numerical examples to validate it. This is followed by the illustration of a 3D analysis of an idealised tunnelling-structure interaction problem, aimed at highlighting some of the features of the proposed masonry model.